Mahri Oral Poetry and Arabic Nabaṭī Poetry: Common core, divergent outcomes - Samuel Liebhaber (Arabian Humanities)
The collections and critical studies of Bedouin vernacular poetry from the Arabian Peninsula (nabaṭī poetry) published over the last century have revealed it to be a dynamic cultural practice whose regional specificities are secondary to its overall coherence. It is also a multilingual tradition. In terms of its topics, motifs and structural template, oral poetry in the Mahri language of Yemen and Oman appears to be closely related to nabaṭī poetry. This article examines various points of intersection between Mahri oral poetry and the regional idioms of Arabic-language nabaṭī poetry, as well as where they diverge from one another. Using the strictly oral poetic traditions of the Mahra as a baseline, the varying impact of written Arabic can be gauged against the vernacular traditions of the Arabian Peninsula as a whole. Thus, this article attempts an historical account of Bedouin oral poetry that interweaves relationships of time, geography and proximity to literary Arabic poetic tradition.